Assessment of disease activity in rheumatoid arthritis with (18)F-FDG PET - Beckers, Catherine; Ribbens, Clio; André, Béatrice; Marcelis, Stefaan; Kaye, Olivier; Mathy, Luc; Kaiser, Marie-Joëlle; Hustinx, Roland; Foidart, Jacqueline; Malaise, Michel G (The Journal of nuclear medicine (1978), 2004)
The aim of this study was to assess synovitis by (18)F-FDG PET in an individual joint analysis and in a global analysis of rheumatoid arthritis (RA) disease activity and to compare (18)F-FDG PET parameters with clinical, biologic, and sonographic (US) rheumatoid parameters. Three hundred fifty-six joints were assessed in 21 patients with active RA: the knees in all subjects and either wrists as well as metacarpophalangeal and proximal interphalangeal joints in 13 patients, or ankles and the first metatarsophalangeal joints in the remaining 8 patients. PET analysis consisted of a visual identification of (18)F-FDG uptake in the synovium and measurements of standardized uptake values (SUVs). Independent assessors performed the clinical and US examinations. PET positivity was found in 63% of joints, whereas 75%, 79%, and 56% were positive for swelling, tenderness, and US analysis, respectively. Both the rate of PET-positive joints and the SUV increased with the number of positive parameters present (swelling, tenderness, US positivity) and with the synovial thickness. The mean SUV was significantly higher in joints where a power Doppler signal was found. In a global PET analysis, the number of PET-positive joints and the cumulative SUV were significantly correlated with the swollen and tender joint counts, the patient and physician global assessments, the erythrocyte sedimentation rate and C-reactive protein serum levels, the disease activity score and the simplified disease activity index, the number of US-positive joints, and the cumulative synovial thickness. (18)F-FDG PET is a unique imaging technique that can assess the metabolic activity of synovitis and measure the disease activity in RA.